2020
DOI: 10.1007/s10029-020-02302-7
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal wall incisional hernia repair improves respiratory function: results after 3 years of follow-up

Abstract: Purpose Hernias severely impact patient quality of life (QoL), and 80% of patients require a surgical operation. Moreover, hernias are responsible for respiratory function alterations. This study aims to investigate the postoperative alterations in respiratory function after open ventral hernia repair in patients with incisional hernia. Methods Patients operated on at the Policlinico “Paolo Giaccone” at Palermo University Hospital between January 2015 and December 2016 were identified in a prospective databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…In another study [22], similar results were found, having 80% of the patients satisfied with their overall results, and chronic pain or recurrence being the main complaints at seven years postoperatively. Complications were registered for 27% of the patients, but mostly between the Clavien-Dindo grades I and II.…”
Section: Types Of Meshsupporting
confidence: 71%
See 1 more Smart Citation
“…In another study [22], similar results were found, having 80% of the patients satisfied with their overall results, and chronic pain or recurrence being the main complaints at seven years postoperatively. Complications were registered for 27% of the patients, but mostly between the Clavien-Dindo grades I and II.…”
Section: Types Of Meshsupporting
confidence: 71%
“…Robotic-assisted surgery [17] LTD mesh [21] Modified Chevrel technique [16] Female gender [24] Absorbable sutures [19] Chronic health diseases [22] Suture fixation without tacks [20] Lack of communication between patients and health personnel [23] MTD mesh [21] Hernia size > 15 cm [11] Male gender [24] Thorough communication between patients and health personnel [23]…”
Section: Positive Factors Negative Factorsmentioning
confidence: 99%
“…Abdominal incisional hernia can lead to respiratory insufficiency and circulatory system dysfunction and even abdominal organ injury, such as intestinal obstruction and intestinal rupture, as well as a negative impact on the stability of the spine and thorax. The quality of life of patients is seriously affected ( van Ramshorst et al, 2012 ; Paulo et al, 2020 ; Sahin et al, 2020 ; Shao et al, 2020 ; Alayon-Rosario et al, 2021 ; Hoffman et al, 2021 ; Jensen et al, 2021 ; Licari et al, 2021 ; Soare et al, 2021 ; Cassese et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%